PRIBADI ISLAM UNTUK MENUNJANG KARAKTER DAN KEPRIBADIAN MANUSIA INDONESIA - Efendi, Sofian (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2023)
Numerous societal issues impact not only our financial circumstances but also our moral fiber and manner of living. The nation's identity and self-confidence have declined, and we still have a ways to go before we reach our lowest point as a religious, amiable, morally pure people. Furthermore, as a consequence of their behavior, student morale is declining. The most crucial factors influencing the caliber of human resources are the traits and ideals acquired from a great education. However, a number of groups have worked to raise society's standards of morality and ethics. There is only one Islamic learning institution there. Regretfully, Islamic instructors must come before morality and personality in society.